Dogme 25: media primitivism and new auteurism in the age of artificial intelligence - Sui, Zhiqiang; Wang, Shuqin (Frontiers in Communication, 2025)
The promulgation of the Dogme 25 Manifesto during the 2025 Cannes Film Festival precipitated significant discourse within the global cinematic community, positioning itself as both an heir to and transcendence of the Dogme 95 movement. Both manifestos serve as critical defenses of cinema’s ontological essence and creative autonomy in their respective technological epochs: digital technology for Dogme 95, and artificial intelligence for Dogme 25. Through the implementation of stringent creative protocols, Dogme 25 presents a formidable resistance to technological alienation in the era of artificial intelligence, while simultaneously reaffirming cinema’s ontological value through the praxis of media primitivism. Moreover, Dogme 25 engenders a reconfigured notion of auteurism within the AI-dominated landscape, emphasizing the resurgence of human subjectivity within a post-human paradigm. Ultimately, this movement elucidates its theoretical contributions and practical implications for preserving and enhancing the ontological and humanistic value of cinema in the age of artificial intelligence.